PELATIHAN SENI KARAWITAN DALAM RANGKA PELAYANAN KEPADA LANJUT USIA DI PERSATUAN WREDATAMA REPUBLIK INDONESIA (PWRI) - Indar Sabri; Joko Winarko; Trisakti Trisakti; Eko Wahyuni Rahayu; Subiyanto Karoso (Program Studi S1, S2, S3 Mananajemen Pendidikan Universitas Negeri Surabaya, 2023)
This increase in the number of elderly people does not only occur in every group of people. This is also the case for retirees, who are now members of the United Wredatama Republik Indonesia (PWRI) organization in Tandes District. The fate of retirees often experiences boredom towards monotonous organizational turmoil and adds to the burden of suffering for them in enjoying old age. So there is a need for activities that can be used as a spirit in living a quality life. The Wredatama Association of the Republic of Indonesia (PWRI) Tandes District has a special policy to provide quality services and uphold the dignity and dignity of the elderly, especially for retirees. One of the impacts of the success of social services is to influence the increase in life expectancy for retirees in the city of Surabaya. Most of the residents in the Persatuan Wredatama Republik Indonesia (PWRI) Kecataman Tandes have a desire to be able to carry out artistic activities as a generator of enthusiasm and at the same time entertaining interactions with fellow residents. Departing from this, the Community Service team of the Department of Ballet, Faculty of Language and Arts, Surabaya State University worked together with the Wredatama Association of the Republic of Indonesia (PWRI) Tandes District to conduct an art training program focused on the type of karawitan art. The activity of presenting karawitan, both tembang and gending music, can entertain and raise the spirit for a quality life.